Effect of temperature on an alga‐grazer trophic transfer: A dual stable isotope (13C, 15N) labeling experiment. (8th May 2018) - Legrand, Erwann; Martin, Sophie; Leroux, Cédric; Riera, Pascal
Abstract: In this study, we examined the impact of temperature on the carbon and nitrogen trophic transfers from a macroalga to a macro‐grazer by the use of dual 13 C‐ and 15 N‐labeling. Using an experimental approach in mesocosms, individuals of the urchin Psammechinus miliaris were maintained for 1 month at 17°C (mean summer temperature in the Bay of Brest) and at 20°C (maximum summer temperature) and fed with 13 C‐ and 15 N‐labeled Solieria chordalis. The results showed that the urchins' 13 C uptake was 0.30 µg 13 C g dry weight (DW) −1 at 17°C and 0.14 µg 13 C g DW −1 at 20°C at the end of the experiment. The lower uptake at the higher temperature may be attributed to a decrease in metabolic activity at 20°C, involving lower feeding and/or respiration rates. Conversely, no significant effect of temperature was detected on 15 N uptake. At the end of the experiment, the urchins' 15 N uptake was 0.04 µg 15 N g DW −1 at 17°C and 0.03 µg 15 N g DW −1 at 20°C. This suggests that temperature may affect carbon and nitrogen trophic fluxes differently. The use of dual isotope labeling offers interesting prospects and needs to be further extended in order to better understand trophic interactions in marine communities and the consequences of current environmental changes, such as global warming.